Поселення епохи пізньої бронзи в Сакському районі Криму - Махнєва, О.О. (Археологія, 1996)
У публікації аналізуються результати досліджень поселень епохи пізньої бронзи поблизу сіл Михайлівка та Іванівка в Криму. В 1977 г. южнее Сакского озера были обследованы три позднесрубных поселения, расположенных у современных сел Михайловка и Ивановка. Керамический материал, полученный в ходе сборов и шурфовок на территории памятников позволяет отнести их к ХI-IХ вв. до н. э. Об оседлости населения и его занятии земледелием свидетельствуют находки зернотерок и кремневого вкладыша серпа. In 1977 three settlements of the late Srubian culture southwards of the Saki Lake near the present-day villages Mikhailovka and Ivanovka were examined. Pottery found during excavations in the territory of the relics permits attributing them to the 11th-9th cent.B.C. Findings of grain graters and a flint insert of a sickle testify to the settled way of life of the population and its agricultural economy.